The Potential of Self-Managed Abortion to Expand Abortion Access in Humanitarian Contexts - Ruvani Jayaweera; Bill Powell; Caitlin Gerdts; Jessica Kakesa; Ramatou Ouedraogo; Uwezo Ramazani; Yohannes Dibaba Wado; Erin Wheeler; Tamara Fetters (Frontiers Media S.A., 2021)
Refugees and displaced people face uniquely challenging barriers to abortion access, including the collapse of health systems, statelessness, and a lack of prioritization of sexual and reproductive health services by humanitarian agencies. This article summarizes the evidence around abortion access in humanitarian contexts, and highlights the opportunities for interventions that could increase knowledge and support around self-managed abortion. We explore how lessons learned from other contexts can be applied to the development of effective interventions to reduce abortion-related morbidity and mortality, and may improve access to information about safe methods of abortion, including self-management, in humanitarian settings. We conclude by laying out a forward-thinking research agenda that addresses gaps in our knowledge around abortion access and experiences in humanitarian contexts.